Toxic Nightlife Relationships, Substance Abuse, and Mental Health: Is There a Link? A Qualitative Case Study of Two Patients - Racionero-Plaza, Sandra; Piñero León, Juan Antonio; Morales Iglesias, Manuel; Ugalde, Leire (Frontiers in Psychiatry, 2021)
Introduction and Aims. This article explores the role of toxic close relationships in night life on substance use disorders and mental health conditions. We also contrast the quality and effects of social relationships when doing drugs with those produced by a mental health program that fosters quality relationships between patients. Design and Methods. This qualitative case study was carried out at a mental health day care centre of a hospital in Malaga (Spain). The cases of two patients with Severe Mental Disorders and a history of drug addiction were analysed. Data was collected through in-depth interviews with every patient, semi-structured interviews about each patient with the psychologist of the medical team of the program, and medical documentation. The analysis involved a combination of inductive and deductive approaches. Results. The analysis of the data revealed, on the one hand, the influence of toxic relationships in nightlife, including violent sporadic sexual relationships, in the initiation and persistence of substance use that took part of the mental health disorder in these patients. On the other hand, the findings show that these participants’ current involvement in a mental health program which fosters quality relationships between patients has brought emotional benefits to both of them. Discussion and Conclusion. This paper points out the relevance of considering quality of social relationships when examining substance use disorders and related mental health problems. Additionally, the findings indicate the importance of fostering quality peer relationships in mental health rehabilitation programs addressed to patients with histories of drug addiction to improve treatment outcome.